Textual Cialis : Four Narratival Strategies for Repairing Disabled Masculinity in the Second Temple Tradition - Cason, Thomas Scott (Biblical interpretation, 2015)
Scholars have overlooked the role that disability plays within Hellenistic Jewish literature. This article looks to fill this gap by analyzing the role of disability in Philo’s Life of Moses, 4 Maccabees, Testament of the Twelve Patriarchs, and the Testament of Job. The essay looks specifically at the interrelationship between masculinity and disability in these documents and the strategies employed within each narrative to repair the disabled male body within them. Each narrative, I argue, employs a unique strategy for restoring the disabled male body. Philo reinterprets Moses’ claim of impaired speech as an indication of his modesty. The writer of 4 Maccabees metaphorically repairs the crumbled bodies of its martyrs by casting them as representational athletes of virtue. Repentance eradicates disablement in the Testament of the Twelve Patriarchs. The Testament of Job provides its hero with a magical prosthesis that restores his body to its previous condition. In demonstrating how these four strategies play out in each narrative, I lay out a methodology for unearthing the able-bodied bias underlying many of our biblical and extra-biblical texts.